2019
DOI: 10.1007/s00415-019-09330-z
|View full text |Cite
|
Sign up to set email alerts
|

Classification of degenerative parkinsonism subtypes by support-vector-machine analysis and striatal 123I-FP-CIT indices

Abstract: Objectives To provide an automated classification method for degenerative parkinsonian syndromes (PS) based on semiquantitative 123 I-FP-CIT SPECT striatal indices and support-vector-machine (SVM) analysis. Methods 123 I-FP-CIT SPECT was performed at a single-center level on 370 individuals with PS, including 280 patients with Parkinson’s disease (PD), 21 with multiple system atrophy-parkinsonian type (MSA-P), 41 with progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The performance of the ANN classifier, with sensitivity and specificity both above 80%, was comparable to that of quantitative olfactory examinations and MIBG myocardiac scintigraphy suggested by diagnostic guidelines. Furthermore, this method is promising because of several advantages: (1) as the sample size of the dataset increases, training results can be further improved; (2) with an adequate number of images taken during the earlier phase of disease (PD or atypical parkinsonian syndromes), the ANN classifier may be trained to identify PD at an early phase [ 24 ] or even possibly at a preclinical phase; (3) medical centers and hospitals can train a site-specific ANN classifier using SPECT images based on their own existing dataset without developing new diagnostic modalities or purchasing expensive machines, especially for places where MIBG is not available; (4) SPECT is more widely available, so that when the diagnosis is not straightforward, physicians tend to order SPECT imaging first to confirm striatal neuron loss, such as to differentiate essential tremors from PD, but not MIBG myocardial scintigraphy before proving a neurodegenerative disease in the early phase; and (5) PD can be differentiated from many disease types of parkinsonism, not just a few Parkinson-plus syndromes or other Lewy body diseases [ 19 , 30 ]. Therefore, this classifier is more applicable when facing uncertain types of parkinsonism in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the ANN classifier, with sensitivity and specificity both above 80%, was comparable to that of quantitative olfactory examinations and MIBG myocardiac scintigraphy suggested by diagnostic guidelines. Furthermore, this method is promising because of several advantages: (1) as the sample size of the dataset increases, training results can be further improved; (2) with an adequate number of images taken during the earlier phase of disease (PD or atypical parkinsonian syndromes), the ANN classifier may be trained to identify PD at an early phase [ 24 ] or even possibly at a preclinical phase; (3) medical centers and hospitals can train a site-specific ANN classifier using SPECT images based on their own existing dataset without developing new diagnostic modalities or purchasing expensive machines, especially for places where MIBG is not available; (4) SPECT is more widely available, so that when the diagnosis is not straightforward, physicians tend to order SPECT imaging first to confirm striatal neuron loss, such as to differentiate essential tremors from PD, but not MIBG myocardial scintigraphy before proving a neurodegenerative disease in the early phase; and (5) PD can be differentiated from many disease types of parkinsonism, not just a few Parkinson-plus syndromes or other Lewy body diseases [ 19 , 30 ]. Therefore, this classifier is more applicable when facing uncertain types of parkinsonism in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…To classify parkinsonism based on DAT-SPECT images, advanced engineering techniques with semi-quantitative analysis have been applied [ 18 ]. In addition, images or signals from striatal regions (SRs) alone can provide adequate differentiating information [ 19 ]. One research group differentiated degenerative parkinsonism using a computer-aided automatic algorithm and SR and whole-brain uptake patterns.…”
Section: Introductionmentioning
confidence: 99%
“…We included the remaining 33 articles (six articles reported PET studies involving 779 patients with PD and 124 controls, and 27 reported SPECT studies involving 1244 PD patients and 859 controls) in this meta‐analysis. These studies comprised cross‐sectional surveys (10 studies), case‐control studies (19 studies), and cohort studies (four studies) 17,22–26,35–61 . Figure 1 illustrates the protocol for the literature search and study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…The selected images are superimposed into a single 2D image, which is called a 2D-combined image hereafter, for disease diagnosis. For example, Prashanth et al [ 1 ], Taylor et al [ 2 ], Oliveira et al [ 3 ], Nicastro et al [ 4 ], and Iwabuchi et al [ 5 ] constructed classifiers for identifying Parkinson’s disease (PD) by extracting features from 2D-combined SPECT images. However, this approach may lose some useful information or features for classification since a 2D-combined image is a projection of the original 3D structure on a specific 2D space.…”
Section: Introductionmentioning
confidence: 99%